Gene Expression of Sperm Associated Antigen 8 and Ran-Binding Protein 9 on Azoospermic Male : Its Association with Spermatogenic Arrest - Christina Agusta Deviana Tanifan; Dwi Anita Suryandari; Luluk Yunaini (Jurnal Health Sains, 2022)
Proteins that play an  important role in the transcription process during spermatogenesis are CREMs that bind to their ACT activators that are suspected to be regulated by SPAG8 and RANBP9. Until now the role of both genes in the spermatogenic arrest process is not known. This study aims to determine the relative expression of Spag8 and RanBP9 on spermatogenic arrest and to analyze the correlation of expression of both genes. This study is a cross sectional study using a sample of testicular biopsy with Johnsen 2 to 8 score. Relative expression analysis of Spag8 and RanBP9 using qRT-PCR technique with Livak calculation. The data obtained were analyzed statistically using ANOVA one way test for Spag8 and Kruskal Wallis test for RanBP9 with significance value p <0,05. The results of this study show that the relative expression of Spag8 and RanBP9 is highest on Johnsen 3 scores and is statistically significantly different (p <0.05). There is a positive correlation with a very strong correlation strength between SPAG8 and RANBP9 expressions. Based on the results of this study shows that both of these genes are candidates for spermatogenic arrest.